Development of Augmented Reality-Assisted Flashcards to Improve Tenth-Grade Students’ Conceptual Mastery in Biology - Raicha Oktafiani; Alvia Syarifah Aini; Aryani Dwi Kesumawardani; Irwandani; Muhammad Farhan Barata (Yayasan Darussalam Bengkulu, 2026)
The development of technology-enhanced instructional media is increasingly important in biology education, particularly for topics that require students to understand abstract ecological processes. This study aimed to develop augmented reality-assisted flashcards and examine their feasibility and effectiveness in improving tenth-grade students’ conceptual mastery of ecosystem components and interactions. The study employed a Research and Development design using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The participants involved material experts, media experts, language experts, biology teachers, and tenth-grade students at SMA Negeri 15 Bandar Lampung, Indonesia. Data were collected through needs analysis questionnaires, expert validation sheets, student response questionnaires, and pre-test and post-test measures of conceptual mastery. The product was developed using Canva and Assemblr Edu to integrate printed flashcards with interactive three-dimensional augmented reality objects. The validation results indicated that the media was highly feasible, with scores of 87.06% from media experts, 89.16% from material experts, and 86.60% from language experts. The effectiveness test showed that students in the experimental class achieved a higher N-Gain score than those in the control class, with an N-Gain of 0.82 in the high category compared with 0.50 in the moderate category. The independent-samples t-test also indicated a statistically significant difference between the two groups, with a significance value of 0.000. These findings suggest that augmented reality-assisted flashcards are feasible and effective as an innovative instructional medium for supporting conceptual mastery in biology learning. The study implies that integrating printed visual media with interactive digital objects can strengthen students’ understanding of abstract biological concepts and provide a more engaging learning experience.